Pengaruh Digital Marketing dan Brand Awareness Terhadap Keputusan Pembelian Produk Skincare Somethinc pada Mahasiswa Universitas Bhayangkara Jakarta Raya - Risma Indah Sari; Dody Kurniawan; Cahyadi Husadha (CV. ITTC INDONESIA, 2026)
This study aims to examine the effect of digital marketing and brand awareness on the purchase decision of Somethinc skincare products among students of Universitas Bhayangkara Jakarta Raya. A quantitative method with a causal-associative approach was employed. The population consisted of active students who had used or purchased Somethinc skincare products, with a sample of 94 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS) using SmartPLS 4.0. The results show that digital marketing has a positive and significant effect on purchase decision (β = 0.569; t = 5.422; p = 0.000), brand awareness has a positive and significant effect on purchase decision (β = 0.316; t = 3.043; p = 0.002), and both variables simultaneously explain 70.1% of the variance in purchase decision (R² = 0.701). These findings indicate that the more effective the digital marketing strategy implemented and the higher the level of brand awareness among consumers, the greater their tendency to decide to purchase Somethinc skincare products, with digital marketing acting as the more dominant predictor.